PENGARUH PENGALAMAN KERJA, INDEPENDENSI, DUE PROFESSIONAL CARE, DAN KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT - Nuur Alif Abdul Muthalib, (2022)
This research was conducted to find out the influence between the relationship of Work Experience, Independence, Due Professional Care, and Competence on Audit Quality. The population in this research is an auditor at the Public Accounting Firm (KAP) of South Jakarta. This research was conducted by analyzing questionnaires from primary data derived from the answers of 52 auditors. The analysis technique used is structural equation model (SEM) using smartPLS 3.0 application with a significance rate of 5%. The results of this research show that the relationship between Work Experience, Independence, Due Professional Care, and Competence has a significant influence on audit quality.